Przemiany ludnościowe na terenie Szwederowa w latach 1874-1914. Analiza demograficzna na podstawie ksiąg zgonów (Kronika Bydgoska, 2021)
The article presents results of demographic studies on deaths in the area of Szwederowo, a rural commune in the Bydgoszcz area, in 1874–1914. Based on them, the author calculated the number of deaths, divided by gender, and their mean number. Other statistics included division of deaths by religion, monthly seasonality, infant mortality among the biggest local denominations, and the number of infant deaths divided by gender and denomination. In addition, death rate and demographic dynamics rate were calculated for selected years. It was noticed that throughout the examined period the number of deaths was increasing due to population growth, and the number of deaths among men was always higher, with the exception of the last period under study. Starting from the 1890s, the number of deaths among Protestants started to drop, whereas it had been rising among Catholics. Analyzing monthly seasonality of deaths, their number was the highest in the summer months and also in October. Infant mortality rate among both Protestants and Catholics was initially increasing and later started to drop, first among Catholics to 239.5 ‰, and later among Protestants to 291 ‰. The number of infant deaths in the two biggest denominations was initially similar; however, starting from the early 20th century, the number of such deaths among Catholics was significantly higher than among Protestants. Mortality rate ranged between 22.1 and 40.5 ‰ and was decreasing, which could hint entering of the population of Szwederowo into another stage of demographic transformation. Starting from the second decade of the 20th century, demographic dynamics rate among Protestants started to drop, whereas it had been clearly increasing among Catholics since the 1890s. Results of the described studies can be used for comparison during analyses of demographic profile in other areas.